2014
DOI: 10.1177/1473325014523818
|View full text |Cite
|
Sign up to set email alerts
|

1000 Voices: Reflective online multimodal narrative inquiry as a research methodology for disability research

Abstract: This article outlines the research approach used in the international 1000 Voices Project. The 1000 Voices project is an interdisciplinary research and public awareness project that uses a customised online multimodal storytelling platform to explore the lives of people with disability internationally. Through the project, researchers and partners have encouraged diverse participants to select the modes of storytelling (e.g. images, text, videos and combinations thereof) that suit them best and to selfdefine w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 46 publications
1
19
0
Order By: Relevance
“…This research confirmed previous work suggesting the role of online methods to reach people with disabilities with less cost and encourage disabled people to talk openly more than face to face (Morris, 2013;Sunderland et al, 2014). Such approach helped in addressing diversity but did not guarantee high numbers of participants probably due to the sensitivity of the topic in this study.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…This research confirmed previous work suggesting the role of online methods to reach people with disabilities with less cost and encourage disabled people to talk openly more than face to face (Morris, 2013;Sunderland et al, 2014). Such approach helped in addressing diversity but did not guarantee high numbers of participants probably due to the sensitivity of the topic in this study.…”
Section: Discussionsupporting
confidence: 83%
“…Another limitation is access by people with limiting disabilities, such as visual and motor impairments, hence the format or length of questions could be tiring or requiring further adjustments (De Cesarei & Baldaro, 2015). Lack of access and socioeconomic status are also key limitations to online research methods (Sunderland et al, 2014). Despite these limitations, the findings in this paper could provide an insight of the potential of using online research methods with vulnerable groups, and will guide future research to do further modifications to ensure overcoming the identified challenges.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2015, we see two papers make specific use of the Internet for research. The first is by Naomi Sunderland (2015) and colleagues and this paper describes a study that made use of the Internet to capture stories from research participants for disability research. The work derives from the 1000 voices project (www.1000voices.edu.au), which established an international web-based platform for 'gathering and displaying digital life stories about the lived experience of people with disabilities ' (2014: 50).…”
mentioning
confidence: 99%